Advances in the Prevention and Treatment of Inflammation-Associated Preterm Birth - Nobuo Masataka (Frontiers Research Topics, 2016)
After decades of intensive research and over 10,000 publications, preterm birth remains a major global obstetric healthcare problem. Each year, early birth is responsible for the deaths of more than one million infants worldwide and is a major cause of life-long disability. Preterm birth places an enormous financial burden on our healthcare systems, resulting in long-term adverse health outcomes and lost productivity for many people. Preterm birth is a syndrome, associated with several different aetiologies; hence, potential treatment strategies need to be matched to pathophysiology in order to be effective. There is now unequivocal evidence that inflammation is causally involved in a majority of spontaneous preterm deliveries. However, the triggers of inflammation, and the strategies by which it can be safely and effectively prevented and treated, remain the subject of ongoing investigation and debate. While intraamniotic infection is an important cause of inflammation-associated preterm birth, particularly in very preterm deliveries, 'sterile' inflammation is actually a more common finding associated with preterm birth. It is likely that the nature, localisation, timing and extent of the inflammatory insult all determine the obstetric outcome and degree of risk to the fetus. These factors will also influence the success of approaches that might be employed to achieve better pregnancy outcomes. Despite our increased understanding of the causes and significance of intrauterine inflammation, we have yet to translate this knowledge into effective therapeutic strategies for preventing prematurity and mitigating its consequences for the neonate. In this Research Topic we review recent progress in treating and preventing inflammation-associated preterm birth, approaching the topic from both the causal and therapeutic perspectives. With global attention increasingly focused on the need to translate knowledge discovery into clinical translation, we hope this EBook will provide a stimulating and timely discussion that will focus research and lead to improved healthcare outcomes for women and children.